Craniofacial Fibrous Dysplasia with Orbital Involvement: Two Rare Case Reports and Comprehensive Review - Marappan, Harikrishnan; Muni, Raja Ayakutty (Archives of Clinical and Medical Case Reports, 2024)
Fibrous dysplasia (FD) is a rare, non-heritable bone disorder where normal bone is replaced by fibro-osseous tissue, leading to structural instability and deformities. This report discusses two cases of craniofacial fibrous dysplasia (CFD) with orbital involvement, presenting the clinical findings, diagnostic challenges, and management strategies. Additionally, a comprehensive literature review is provided to offer insights into the pathophysiology, clinical manifestations, and treatment options for this condition.